The Influence of JOMO and Authenticating News Before Sharing on Fake News Sharing Behavior - Aliva Brilliant Al-Aufar (Metacommunication: Journal of Communication Studies, 2024)
Easy access to the internet provides many conveniences for its users. Thanks to the convenience provided, information can spread quickly and widely. However, for every advantage there are disadvantages. The easy dissemination of this information can also have negative impacts, one of which is the spread of fake news. Currently, fake news is very easy to find, especially in online media. This research is based on behavioral reasoning theory, which discusses the reasons behind individual behavior and intentions. The purpose of this theory is to find out the factors that influence the spread of fake news. In this research, there are 2 factors studied, JOMO and authenticating news before sharing through perceived believability. By distributing questionnaires to students and analyzed using SmartPLS, it can be concluded that JOMO and authenticating news before sharing have a negative effect on fake news-sharing intentions either through mediation or directly. The results show that individuals will not have the intention to spread fake news even though the person believes that the source of the information they receive is credible. Based on this research, individuals tend to check the veracity of the news they receive before sharing it to avoid fake news-sharing behavior. Apart from that, there are also some individuals who feel happier and more relaxed when they are not connected to information that is being widely reported, this is their reason not to engage in fake news-sharing.